ANCAMAN KEAMANAN NON-KONVENSIONAL DI PULAU TERLUAR INDONESIA: KASUS KEPULAUAN MOROTAI - Poltak Partogi Nainggolan (Jurnal Politica, 2011)
Remote and outer Islands of Indonesia still have not been properly taken care by the central government although they recently confronted crucial threats from other countries. This field research attempted to disclose potential threats in Morotai, an Indonesian strategic island in the Pacific Ocean. Applying a combination of approaches, library study and in-depth interview, the research describes not only main (conventional) security threats, but also non-conventional ones. Its analysis which uses a qualitative method has explained the recent situation in the Municipality of the Morotai Archipelago. The research finding explains how serious the conventional security threats in Morotai as a newly enlarged municipality.